2017
DOI: 10.3832/ifor2342-010
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of tannin extraction from spruce bark

Abstract: (1)Tannins have shown antifungal effects and have been considered a potential natural compound for wood preservation. Extracts produced from softwood bark contain both tannins and non-tannin compounds, which may reduce the effectiveness of tannin used as a wood preservative. The purpose of this research is to study the environmental impact of hot water extraction, identify the hot spots within the tannin cradle-to-gate life cycle and give suggestions to optimize its environmental profile. Different extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
5
23
0
Order By: Relevance
“…functional units, system boundaries, product allocation and impact assessment methods) and the next citations are reported only for scaling purposes and further comparisons would not be correct. For example, considering weight as a functional unit, Ding et al 22 reported approximately 4 kg CO 2 eq per kg of extracted tannins at laboratory scale, while Modahl et al 18 reported approximatively 1 kg CO 2 eq per kg of extracted vanillin (at full industrial scale).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…functional units, system boundaries, product allocation and impact assessment methods) and the next citations are reported only for scaling purposes and further comparisons would not be correct. For example, considering weight as a functional unit, Ding et al 22 reported approximately 4 kg CO 2 eq per kg of extracted tannins at laboratory scale, while Modahl et al 18 reported approximatively 1 kg CO 2 eq per kg of extracted vanillin (at full industrial scale).…”
Section: Resultsmentioning
confidence: 99%
“…In this field, LCA has been mainly used to evaluate full-scale bioenergy production (mainly bio-ethanol 18 , biogas 19,20 , jet fuel 21 ) and to a lesser extent the production of chemicals like polysaccharides 5 or tannins 22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anionic and cationic charge density of tannins and cationic cellulose nanocrystals (CCNC) 104 were determined using polyelectrolyte titration with particle charge detector (PCD). 0.01% 105 (w/w) tannin and cationic cellulose nanocrystals solution were prepared at different pH (3)(4)(5)(6)(7)(8)(9)(10) and titrated with poly-diallyldimethylammonium chloride and sodium polyelectrolyte sulphonate. All dilutions were done using same buffer solutions used for tannin and nanocrystal sample preparation.…”
Section: Determination Of Charge Density Zeta Potential and Conductimentioning
confidence: 99%
“…Proanthocyanidins such as tannins and other flavonoids are a group of bio-based chemicals traditionally extracted from plant seeds, berry or fruit skins, tree heartwood or bark and novel means to valorize these especially from industrial side streams are ongoing [1][2][3][4][5] . These phenolic, secondary metabolic compounds in plants have traditionally been used in leather industry due to the protein binding capacity and more recently in colloidal complexes intended for food, pharma, 6 chemical and wood product industries [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%